The Impact of Dehydration and Initial HCI on HCI Null Cycles and Antarctis Stratospheric Ozone Loss in the Core of the Vortex - Zhang, Yiran (2022)
The Antarctic ozone hole is a phenomenon of substantially reduced polar ozone that reoccursevery winter and spring over Antarctica since many decades (M¨uller et al. 2018). Polarozone depletion is driven by anthropogenic chlorine and bromine substances released to theatmosphere due to human activities. The Montreal Protocol has been successful in controllingstratospheric chlorine loading, the first signs of declination in stratospheric halogen andrecovery of the Antarctic ozone hole are observed around year 2000. However due to the longlifetime of chlorine source gases, they are still causing and will be causing ozone depletionin the foreseeable future.The characteristics of the global total column ozone field can be reproduced Chemistryclimatemodels, however the simulation of the Antarctic ozone hole is often not satisfactorydue to deficiencies in the model dynamics or in the stratospheric chemistry scheme (Dhomseet al. 2018).Chlorine species in the atmosphere exist mainly in the form of HCl and ClONO2. Stratosphericozone depletion requires these so-called reservoirs to convert into active chlorinespecies by heterogeneous reactions on polar stratospheric clouds (PSCs) and cold sulphateaerosol particles (WMO 2018). Ozone depletion occurs in the presence of light, which firstreturns in early spring in the Antarctica, this time period is characterised by further activationand maintenance of high levels of active chlorine(M¨uller et al. 2018.In this thesis, we follow earlier work [Grooß et al., 2011, M¨uller et al., 2018, Zafar et al.,2018] on the chemical processes in the core of the vortex, in the lower stratosphere (16 –18 km, 85–55 hPa, 390–430 K), where extremely low ozone mixing ratios are reached. Inthese studies the ”HCl null cycles” were intensively studied. However, two aspects wereneglected in the previous study: namely the impact of Antarctic dehydration (Kelly et al.1989, Nedoluha et al. 2002, Poshyvailo et al. 2018, Rolf et al. 2015, Schoeberl and Dessler2011, V¨omel et al. 1995) and HCl destruction ...